Armed conflict, community-based cash transfers, and social cohesion: Evidence from a randomized intervention in Ethiopia - Abay, Kibrom A.; Nigus, Halefom Yigzaw; Tabe-Ojong, Martin Paul Jr. (Household in Conflict Network, 2025)
Amid a surge in armed conflicts in Africa, the impact of armed conflicts on social cohesion and potential avenues to rebuild social cohesion in conflict-affected settings remain active areas of inquiry. Most importantly, identifying instruments and interventions that can effectively strengthen social cohesion in conflict-affected settings can inform and facilitate peace-building efforts. We examine whether community-based cash transfer and social protection programs can strengthen social cohesion in settings grappling with the adverse effects of armed conflict. We answer this question using the 2020 civil war in Ethiopia and combining this with a randomized community-based cash transfer program rolled out after the conflict. Exploiting temporal variation in the spread of large-scale armed conflicts (battles) across a two-wave panel survey, we show that battles are associated with a deterioration in social cohesion. Reassuringly, we demonstrate that a modestly sized community-based cash transfer can rebuild and restore social cohesion in communities grappling with armed conflict and deterioration in social cohesion. Heterogeneity analysis shows that households who belong to a minority ethnic group in each community reported a higher loss in social capital associated with their exposure to armed conflict and that the community-based cash transfer appears to be more effective in rebuilding social cohesion among these households.